Artistic expression of historical theme in works - Saida Matnazarova (International Journal Of Literature And Languages, 2025)
This article explores the artistic expression of historical themes in various creative works, such as literature, painting, and film. By examining how historical events, periods, and figures are conveyed through aesthetic choices, narrative structure, and symbolic elements, the paper underscores the significance of artistic interpretation in shaping public perception of the past. In many cases, the artist’s personal vision, cultural context, and intended audience contribute to a reimagining or reinterpretation of historical realities. Through close analysis of representative examples, the study highlights the balance between factual accuracy and imaginative freedom, demonstrating how art can provide deeper insight into historical phenomena, evoke empathy, and provoke critical thinking. Ultimately, the artistic rendering of historical subject matter serves not only to commemorate and educate but also to encourage dialogue about collective memory and cultural identity.